Capaian Perkembangan Kognitif Anak Penyintas Kekerasan Verbal Domestik yang Semakin Intensif Selama Pandemi - Devi Tri Alviani; Anastasia Widjaja; Muhammad Hafizh Tri Wahyu; Ike Herdiana (Universitas Kristen Maranatha, 2021)
This research is conducted to describe child’s cognitive development who survived domestic verbal abuse, which become more intensive during pandemic. Qualitative data were collected from observations and interviews at Surabaya, Sleman, and Jakarta, also supported by intelligence test’s score of child participants. Participants were chosen using purposive sampling technique with inclusion criteria consists of parents and his/her child aged 7-12 years old indicated experiencing domestic verbal abuse during pandemic. Data were analyzed using content analysis technique for observation notes and data-driven thematic analysis for interview results. Result shows that participant families were lack of self-disclosure and went through some pressure during pandemic. There aren’t any serious problem on assimilation and abstraction performances, nor cognitive task development fulfillment. However, most of the child participants have inadequate accommodation and problem solving performances. Intelligence test’s score categorization also shows that child participants surprisingly have high category of intelligence compared with children their age. Keywords: cognitive development, domestic verbal abuse, abuse on children, negative parenting